Karakterisasi Produk Metalurgi Serbuk Berbahan Limbah Aluminium Paduan dan Kaca - Alit Triadi, Anak Agung; Okariawan, I Dewa Ketut; Nursaid, Nursaid (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Aluminum alloy and glass waste is often found in the business of making display racks. It is necessary to do research on the utilization of waste into useful products. This study aims to determine the hardness and compressive strength of objects made of a mixture of aluminum alloy and glass using the powder metallurgy method. The first stage was making aluminum and glass powders up to 100 mesh in size, the next stage was mixing the powders (mixing) with time variations of 70 minutes, 80 minutes and 90 minutes with a composition of 80% aluminum and 20% glass. Then manufacture of specimens with a compaction load of 8 tons. Furthermore, the sintering process at a temperature of 500 oC with time variations of 60 minutes, 90 minutes and 120 minutes, then tested hardness and compressive strength. The results obtained from the hardness test and compressive strength test showed the highest value for the test object with variations in the stirring time and sintering time of 90 minutes. Based on the two-way ANOVA analysis, the mixing time and sintering time obtained the values of Fcount>Ftable, so that the mixing time and sintering time have a significant effect on hardness and compressive strength.